Assessment of the zonal asymmetry trend in Antarctic total ozone column using TOMS measurements and CCMVal-2 models - Siddaway, J.; Klekociuk, A.; Alexander, S.P.; Grytsai, A.; Milinevsky, G.; Dargaville, R.; Ivaniha, O.; Evtushevsky, O. (Ukrainian Antarctic Journal, 2020)
In the paper the seasonal trends in the zonal asymmetry in the quasi-stationary wave pattern of total ozone column (TOC) at southern polar latitudes have been investigated. We evaluated and compared seasonal trends in the zonal TOC asymmetry from modern era satellite measurements using the Total Ozone Mapping Spectrometer data and the second Chemistry Climate Model Validation (CCMVal-2) assessment. The model longitude phase shifts in asymmetry are in general consistent with the eastward phase shifts observed in historical period 1979–2005, however, there are underestimated values in individual seasons. Future trends in zonal asymmetry from the eleven CCMVal-2 models up to 2100 are presented. They demonstrate the appearance of reverse (westward) future phase shifts, mainly in austral summer. The results are in agreement with previous study and highlight that the general eastward/westward phase shift is caused by both greenhouse gases changes and ozone depletion/recovery. The greenhouse gases change drives a basic long-term eastward shift, which is enhanced (decelerates or reverses) in austral spring and summer by ozone depletion (recovery). The trends in the TOC asymmetry are forced by a general strengthening of the stratospheric zonal flow, which is interacting with the asymmetry of the Antarctic continent to displace the quasi-stationary wave-1 pattern and thus influences the TOC distribution. The results will be useful in prediction of seasonal anomalies in ozone hole and long-term changes in the local TOC trends, in ultraviolet radiation influence on the Southern Ocean biological productivity and in regional surface climate affected by the zonally asymmetric ozone hole.